Seven pillars of wisdom : a triumph - Lawrence, T. E. (Thomas Edward), 1888-1935.; Lawrence, A. W. (Arnold Walter), 1900-1991.; Kennington, Eric, 1888-1960.; John, Augustus, 1878-1961.; Roberts, William, 1895-1980.; Sargent, John Singer, 1856-1925.; Nicholson, William, 1872-1949.; Lamb, Henry, 1883-1960.; Rothenstein, William, 1872-1945.; Young, R. M.; Gill, Colin, 1892-1940.; Dobson, Frank, 1886-1963.; et al. (New York : Anchor Books, 1991)
The classic account of the Arab tribes' guerrilla warfare against Turkish forces during World War II and of Lawrence's part in and reflections on that warfare.
Discovery of Feisal -- Opening the Arab offensive -- Railway diverson -- Extending to Akaba -- Marking time -- Raid upon the bridges -- Dead sea campaign -- Ruin of high hope -- Balancing for a last effort -- House is perfected.
"First Anchor Books edition: July 1991".
"Originally published in a private edition by the George Doran Publishing Company in 1926. It was first published in the United States for general circulation by Doubleday, Doran & Company in 1935."--T.p. verso.
Reprint of the 1935 Doubleday, Doran edition (O'Brien A054).
Preface by A.W. Lawrence.
Includes indexes.
O'Brien, P.M. T.E. Lawrence
Keywords: World War, 1914-1918 -- Campaigns -- Turkey and the Middle East; World War, 1914-1918 -- Campaigns -- Arabian Peninsula; Arab countries -- History -- Arab Revolt, 1916-1918.; World War, 1914-1918 -- Personal narratives, British; Lawrence, T. E. -- 1888-1935.; Soldiers -- Great Britain -- Biography; Arabs -- History -- 20th century; Bedouins -- History -- 20th century; Wahhabiyah -- Saudi Arabia; Arabian Peninsula -- Social life and customs